2011, No. 9, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Auditing theory and practiceJonas Mackevičius, Danutė Adomavičiūtė, Peculiarities and role of Lithuanian customs audit in the customs control process, 7Irmantas Aleliūnas, Zenona Atkočiūnienė, Information audit: modelling of standards structure, 18Vaclovas Lakis, Financial information,  reasons and methods of manipulations, 33Accounting theory and practiceIndrė Kalinovaitė, Kristina Rudžionienė, Recognition and valuation of goodwill in accounting of Lithuanian companies, 46Asta Mockevičiūtė, Kristina Rudžionienė, The impact of accounting policy on earnings management, 54Justina Aleliūnaitė, Izolda Bučytė, Organization of accounting system in China, 62Erika Gerasimovič, Jurgita Kunigėlytė, Organization of accounting in the Republic of Moldova, 71Economical problemsAlina Warelis, Analysis of changes in resources and productive functions of forests in Poland, 84Donatas Ratkevičius, Software related criteria for selecting enterprise resource planning systems, 97Rasa Subačienė, Analysis of travel agencies and travel operators‘ activity, 112Vilius Savickas, Target costing: significance,  principles and stages, 119Jonas Martinavičius, Reda Blažaitytė, Reliability and validity assessment in financial ratios analysis, 137Rasa Kanapickienė, Development of models of internal control, 157ReviewsDaiva Raziūnienė, Audit and analysis of financial statement: professional approach to financial statements, 172
Keywords: none